Decision Support System for Determining Underprivileged Communities as a Government Guide in the Family Hope Program - Marindi, Elsa (PT. Lentera Ilmu Publisher, 2024)
This study addresses the economic disparity in Indonesia by enhancing the selection process for beneficiaries of the Family Hope Program (PKH), a government initiative providing financial assistance to very poor households. Traditionally, the selection process is manual and prone to inefficiency and fraud. To improve objectivity and accuracy, a Decision Support System (DSS) utilizing the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method is proposed. TOPSIS ranks households based on multiple welfare criteria, such as income, housing conditions, and basic amenities, identifying those closest to the ideal solution. The system effectively prioritizes aid distribution by assigning a closeness coefficient to each household, enabling a more efficient allocation of resources. The results show that households with the highest coefficients, such as V1 (0.637367819), are prioritized for assistance, while those with lower scores, like V7 (0.139295032), are ranked lower. This method ensures that government aid reaches the most underprivileged communities.